2006
DOI: 10.1007/s11430-006-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic subduction-accretion zone in northeastern south china sea inferred from geophysical interpretations

Abstract: A segment of Mesozoic subduction-accretion zone was inferred across the northeastern South China Sea at approximately NE45° orientation. Basic evidence includes the following: A belt of peek gross horizontal Bouguer gravity gradient (PGHGBA) is comparable in size and intensity to that of the Manila subduction-accretion zone. A belt of high positive magnetic anomalies appears to the north and sub-parallel to the PGHGBA, representing the volcanic arc associated to the subduction zone. The PGHGBA crosses obliquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 14 publications
3
76
0
Order By: Relevance
“…Seismic reflections are correlated with well data from MZ-1-1 (Hao et al 2001;Yan and Liu 2004;Yan et al 2014;Fig. 3) and interpretations of nearby seismic profiles by Zhou et al (1995Zhou et al ( , 2006Zhou et al ( , 2008 and Zhu et al (1999). Drilling and logging data of well MZ-1-1 were acquired by industrial standards and are provided by TCPOC.…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…Seismic reflections are correlated with well data from MZ-1-1 (Hao et al 2001;Yan and Liu 2004;Yan et al 2014;Fig. 3) and interpretations of nearby seismic profiles by Zhou et al (1995Zhou et al ( , 2006Zhou et al ( , 2008 and Zhu et al (1999). Drilling and logging data of well MZ-1-1 were acquired by industrial standards and are provided by TCPOC.…”
Section: Methodssupporting
confidence: 65%
“…The beginning of the drift phase, oriented north-south, is marked by a major breakup unconformity (BUU; Zhu et al 1999;Zhou et al 2006;Wang and Li 2009; Table 1). Marine magnetic anomalies in the SCS were identified to be from anomalies 11 to 5d (Taylor and Hayes 1983).…”
Section: Study Area and Regional Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…As one part of the Pearl River Mouth basin, Chaoshan Depression is proved to be quite different from its neighbors by containing very thick Mesozoic sediments and a thin Cenozoic layer (Li et al 2008a, b). According to the widespread distribution of the subduction related granites onland and in Dongsha area as well as the associated compressive deformation, scientists believed that there once existed a late Mesozoic subduction zone along the southeastern China continental margin (Jahn et al 1976;Hilde et al 1977;Hamilton 1979;Zhou and Li 2000;Zhou et al 2006Zhou et al , 2008, and Zhou et al (2006Zhou et al ( , 2008 suggested that the Chaoshan Depression used to sit at the forearc of the subduction system. The 2D Velocity and Density Structure of the Mesozoic Sediments also show that there is a huge fault dipping toward north at the south of the Chaoshan Depression, which is deduced to be related to the Mesozoic subduction (Ruan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 The Paleogene tectonic units of the Pearl river Mouth basin (adapted after Pang et al 2005). I Panyu Low Uplift, II Yunkai Low Uplift, III Dongsha Uplift, IV Baiyun Sag, V Huizhou Sag, VI Xingning Sag, 1 city, 2 boundary of Pearl River Mouth Basin, 3 boundary of first-order tectonic unit, 4 boundary of second-order tectonic unit, 5 NW-strike fault magnetic data and the faults distribution, Chen et al (2005) and Zhou et al (2006) concluded that the Pearl River Mouth Basin was located to the north of the Mesozoic Western Pacific Plate subduction zone, and that the regional stress field vitally transformed from left-lateral transpression to right-lateral transtension in the Late Cretaceous.…”
Section: Geological Backgroundmentioning
confidence: 99%